Empowering MSME Performance Through Fintech and E-Commerce: The Moderating Role of Cashless Society - Ilham, Ratih Milati; Yarisma, Fithri Widyanita; Setiawati, Ira; Putri, Darajatus Zakia; Ainiyah, Erika Rodhotul; Munaji, Khoirul (MAKSIMUM: Media Akuntansi Universitas Muhammadiyah Semarang, 2025)
This study explores the impact of fintech payment and e-commerce adoption on the performance of Micro, Small, and Medium Enterprises (MSMEs), focusing on the moderating role of the cashless society. Using a quantitative approach, data were collected from MSMEs operating in Central Java to examine how digital financial solutions influence business performance. The findings reveal that fintech payment adoption enhances MSME performance by improving transaction efficiency, financial management, and access to a broader market. However, e-commerce adoption does not directly affect MSME performance, which may be attributed to challenges such as technological readiness, digital literacy, and infrastructure limitations. The cashless society strengthens the impact of fintech payments on MSME performance, indicating that the shift toward digital transactions provides competitive advantages for MSMEs. However, its role in moderating the effect of e-commerce on MSME performance remains limited, suggesting that successful e-commerce adoption requires additional supporting factors. These findings underscore the importance of digital payment integration for MSMEs and highlight the need for financial literacy programs, digital mentoring, and infrastructure development to support MSMEs in adapting to an increasingly digital economy. This study provides valuable insights for policymakers, financial institutions, and MSME stakeholders in shaping strategies to enhance digital transformation and financial inclusion in the MSME sector.